Sosialisasi Program Studi Ekonomi Pembangunan Fakultas Ekonomi Universitas Borneo Tarakan Di Kabupaten Nganjuk Jawa Timur - Agus Tri Darmawanto; Zakaria Basran; Bernadeth Yosephine Priskilla Br Simangunsong; Adhy Satya Pratama (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Socialization of the Development Economics Study Program is a key strategy in expanding access to information and increasing participation in higher education. This article describes the implementation of the socialization activity for the Development Economics Study Program, Faculty of Economics, Borneo Tarakan University, in Nganjuk Regency, East Java. The main objective is to introduce the study program's profile, career opportunities, and its role in supporting the development of Indonesia’s border regions. The activity was conducted through presentations, interactive discussions, and the distribution of promotional materials. The results revealed a high level of enthusiasm among high school students and local stakeholders, along with an improved understanding of the importance of Development Economics studies. This socialization effort contributed to enhancing the positive perception of Borneo Tarakan University as a strategic higher education institution supporting national development from the border.